Social Infrastructure Finance and Institutional Investors. A Global Perspective - Georg Inderst (ZBW – Leibniz Information Centre for Economics, 2020)
Social infrastructure has endured a long period of neglect in most developed and emerging countries, with chronic underinvestment exposed by the coronavirus crisis 2020. The financial crisis 2007/08 led to a slow revival of economic infrastructure policies, and a growing involvement of institutional investors. In contrast, private sector investment in social infrastructure has widely fallen back over the last decade. Will the next decade see a renaissance of - public and private - social infrastructure investment? This is the first systematic account of social infrastructure investment from an international perspective, leading to several key conclusions for policy makers and investors. The public sector will remain the dominant source for funding and financing. Nonetheless, much more private capital could flow with greater clarity on social assets, given their very diverse characteristics across sectors and projects. Several investment strategies can realistically be improved and expanded. Sustainability, impact and SDG investing open a new door for asset owners.
Keywords: E22; F21; G15; G18; G2; H54; H57; H75; O16; O18; R31; R51; 330; social infrastructure; infrastructure investment; infrastructure finance; infrastructure policy; public-private partnerships; institutional investors; health infrastructure; infrastructure funds; sustainability investing; impact investments